Application of big data technology in prediction and prevention of rock burst. (September 2020) - Shi, Junwei; Meng, Xiangrui; Chen, Zhangliang; Wu, Xueyi
Abstract: Coal and rock dynamic disasters, especially the impact ground pressure dynamic disasters, are major safety technical problems in deep resources mining in China. In view of the basic theory and key technology of ground pressure monitoring and early warning during coal mining, in order to reveal the scale and timing effect of physical field response and the relation with energy accumulation-release, the cooperative relation and equivalent transformation mode of multi-field multi-parameter precursor information, constructing the monitoring and warning index system, big data technology is used to study the characteristics of ground pressure stress-energy-physical parameter coupling feed-off and time-space evolution, while considering the whole mechanical process of ground pressure development, and establish the theory and model of multi-field multi-parameter monitoring and early warning under the background of big data based on space-time complementarity; The purpose of this paper is to establish the theory and method of intelligent identification and early warning of impact ground pressure through studying the intelligent identification method and expert system of the main control factors, disaster risk and precursor information of impact ground pressure under big data. In order to ensure the correctness and accuracy of monitoring information, construct the integrated monitoring and warning technology of shock ground pressure-electric-seismic multi-source information under the complex geological conditions of coal mine, this paper on the one hand studies the accurate monitoring, extraction and identification theory and optimization algorithm of shock ground pressure precursor information based on multi-parameter information fusion, on the other hand develops the active controllable stress inversion technology and equipment based on vibration wave CT, the continuous real-time monitoring theory method of ground stress, and ultra-low frequency electromagnetic radiation monitoring technology. Finally the theory and technology system of impact ground pressure risk identification and monitoring can be concluded.